Using legitimacy dialogues to explore responses to flooding issues in a UK catchment - Gearey, Mary; Jeffrey, Paul (Water and environment journal : WEJ, 2010)
A growing awareness of the potential impacts of climate change has led to the consideration of a variety of future outcomes by water supply companies, regulators and local authorities within England and Wales. These strategies recognise the possibility of episodes of flooding within catchments, with the Environment Agency's fourth Periodic Review requiring water companies to explore future demand and supply scenarios up to 2030. However, there is a gap in the literature concerning how those tasked to implement water policy, and those subject to it, view these change scenarios. This paper outlines a study undertaken within the River Nene catchment, exploring how water resource governance bodies and water users respond to flooding issues. In particular, the research focuses on the twin concepts of legitimacy and dialogue as a means to assess the boundaries of stakeholder engagement with these strategic change scenarios.